2015
DOI: 10.1371/journal.pone.0122515
|View full text |Cite
|
Sign up to set email alerts
|

Reference Gene Validation for RT-qPCR, a Note on Different Available Software Packages

Abstract: BackgroundAn appropriate normalization strategy is crucial for data analysis from real time reverse transcription polymerase chain reactions (RT-qPCR). It is widely supported to identify and validate stable reference genes, since no single biological gene is stably expressed between cell types or within cells under different conditions. Different algorithms exist to validate optimal reference genes for normalization. Applying human cells, we here compare the three main methods to the online available RefFinder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
191
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(201 citation statements)
references
References 29 publications
10
191
0
Order By: Relevance
“…In order to correct for this, we manually adjusted the raw Ct-values for efficiencies before analysis. This has previously proved to make results obtained with the RefFinder software comparable to those obtained with the stand-alone applications22. Similar and comparable evaluations are obtained from the Genorm, NormFinder, and the ΔCt-methods, with deviations for some genes obtained from BestKeeper.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…In order to correct for this, we manually adjusted the raw Ct-values for efficiencies before analysis. This has previously proved to make results obtained with the RefFinder software comparable to those obtained with the stand-alone applications22. Similar and comparable evaluations are obtained from the Genorm, NormFinder, and the ΔCt-methods, with deviations for some genes obtained from BestKeeper.…”
Section: Discussionsupporting
confidence: 60%
“…RefFinder, a free online software platform for identification of stable RGs, derives a comprehensive ranking based on the geometric mean of the scores from Genorm, BestKeeper, NormFinder, and the ΔCt-method in order to extract the best RGs based on the different mathematical approaches20. Although these methods differ in their mathematical design, studies have shown only small variations in the outcomes for Genorm, NormFinder, and BestKeeper, and also between the stand-alone applications for Genorm, NormFinder, and BestKeeper, and RefFinder, making these methods comparable2122.…”
mentioning
confidence: 99%
“…Moreover, geNorm and NormFinder were also in agreement on the least stable gene for each treatment. The accordance in the results provided by these algorithms was also mentioned in some previous study on other plants (De Spiegelaere et al, 2015; Mafra et al, 2012). However, obvious divergence in these results still exists in some situations, mainly caused by the varying priorities in different algorithms.…”
Section: Discussionsupporting
confidence: 87%
“…Herein, we have employed geNorm, first developed by Vandesompele, et al [34], and NormFinder statistical programs to access the stability of candidate reference genes. Both retrieved highly comparable results, especially in terms of gene stability ranking [51]. Accordingly, we have identified B2M and HPRT as the most stable reference genes to address the impact of oxygen shortage in hypoxic bladder cancer cells, irrespectively of their molecular nature.…”
Section: Discussionmentioning
confidence: 93%